Mentoring 1, 2, 3, 4: A look at the key resources: Training manual nº 2 - Alves, Ana Berta (2023)
Mentoring is directed to personal and professional development and can take various forms, ranging from the involvement of different relationship styles and mentor-mentee profiles, to the variety of resources and practices. The +Mentoria(s) Project presents the training manual no.2, Mentoring 1,2,3,4: A look at the key resources. This guide focuses on three aspects: 1) Peer mentoring, in which experiences, identities, hopes, concerns and learning are shared with colleagues who, despite being in a similar situations, have a different knowledge or practice in some area. It provides a specific form of help and support for problem solving and constitutes a powerful way to make progress. 2) The Grow Theory, a planning resource emerged from coaching. 3) The ethical principles of mentoring that guide this relationship model. It also includes a set of useful resources, including the Empathy Map and suggestions for peer mentoring work. Keywords: mentoring, peer mentoring, Grow Theory, mentoring ethics, mentor, mentee, mentoring relationship, mentor typology, mentee typology, inclusion.